A Single-Center Study on the Outcomes of Target Limb Revascularization in Femoropopliteal Lesions Treated With Drug Coated Balloons and Bare Metal Stents. (December 2022) - Linehan, Victoria; Doyle, Maria; Barrett, Brendan; Gullipalli, Ravindra
Purpose: Multiple randomized controlled trials have shown that both drug coated balloons (DCBs) and bare metal stents (BMSs) significantly reduce restenosis in femoropopliteal lesions compared with plain balloon angioplasty. However, few studies have directly compared DCB and BMS treatments. Therefore, the goal of our study was to determine if the rate of target lesion revascularization (TLR) differs between DCB and BMS treatment at our center. Materials and methods: We performed a retrospective chart review of femoropopliteal interventions at a single center from 2009 to 2017. The intervention, patient and lesion characteristics, and TLR events were recorded. Exclusion criteria were loss of follow-up, death, bail-out stenting, and amputation within 60 days of treatment. Freedom from TLR was analyzed over a 3 year period with Kaplan-Meier survival curves. Cox hazard ratios were calculated to account for patient and lesion characteristics. Results: A total of 322 lesions (234 patients) treated with DCBs and 225 lesions (194 patients) treated with BMSs were included in this study. There were significant differences in baseline patient and lesion characteristics between groups—a greater proportion of women, patients with dyslipidemia, and lesions with popliteal involvement were treated with DCBs. There was no difference in the freedom from TLR between DCBs and BMSs. Accounting for patient and lesion characteristics, there was still no difference between DCBs and BMSs on the hazard of TLR. While our analysis did not detect a difference in the rate of TLR, there was a significant difference in the type of TLR. Compared with DCBs, a greater proportion of lesions initially treated with BMSs were retreated via surgical bypass rather than endovascular intervention, suggesting that lesions treated with DCBs may be more amenable to future endovascular intervention. Conclusion: Our retrospective analysis showed no difference in the rate of TLR between lesions treated with DCBs and BMSs. However, DCBs were more often used in complicated lesions involving popliteal arteries and may also allow for easier endovascular reintervention.